2017
DOI: 10.1080/10408398.2015.1087379
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical modification of starches: A review

Abstract: The development of green material in the last decade has been increased, which tends to reduce the impact of humans on the environment. Starch as an agro-sourced polymer has become very popular recently due to its characteristics, such as wide availability, low cost, and total compostability without toxic residues. Starch is the most abundant organic compound found in nature after cellulose. Starches are inherently unsuitable for most applications and, therefore, must be modified physically and/or chemically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(95 citation statements)
references
References 168 publications
0
93
0
2
Order By: Relevance
“…The high values of chewiness for chestnut hydrogels is a drawback from the food point of view that could be overcome blending the starch with other biopolymers. In contrast, high springiness values could make it suitable for food packaging purposes (Zia‐ud‐Din et al ., ). Springiness results were related those found from SAOS, Figure S2 shows the linear relationship found between elastic properties ( G ′) and the ratio D 1 / D 2 (being D the distances to each peak in TPA) previously reported (Lagarrigue & Alvarez, ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The high values of chewiness for chestnut hydrogels is a drawback from the food point of view that could be overcome blending the starch with other biopolymers. In contrast, high springiness values could make it suitable for food packaging purposes (Zia‐ud‐Din et al ., ). Springiness results were related those found from SAOS, Figure S2 shows the linear relationship found between elastic properties ( G ′) and the ratio D 1 / D 2 (being D the distances to each peak in TPA) previously reported (Lagarrigue & Alvarez, ).…”
Section: Resultsmentioning
confidence: 97%
“…In this context, physically modified starch by several methods such as micronisation, drum drying, heat‐moisture and annealing treatment can be safely employed in food products (Molavi et al ., ). Pregelatinised starch is the most common modified starch with many applications in food industry, but the features depend on the gelatinisation conditions (Zia‐ud‐Din et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…To enhance the structural and functional quality of these starches and achieve better results in various formulations, the researchers suggest some modification in their structure. Several studies have been reported on the improvement of functional quality of starch by physical, chemical or mechanical modifications [23,43,45,48,[50][51][52][53][54][55][56][57][58]. However, some environmental and processing factors may reduce the functional quality of starch by various modifications during storage and processing [57].…”
Section: Starch Modificationmentioning
confidence: 99%
“…Starch is the main reserve of polysaccharide in plants and probably the second most common carbohydrate in nature, after cellulose. It can be found in different plant sources like seeds, the stalk or the root (Alcázar-Alay & Meireles, 2015;Eliasson, 2006;Zia-ud-Din, Xiong, & Fei, 2017). Starch is formed in the chloroplasts of green leaves and amyloplasts, and is stored in organelles of grain and tuber and is used as a source of carbon and energy in plants.…”
Section: Introductionmentioning
confidence: 99%